1978
DOI: 10.1073/pnas.75.11.5692
|View full text |Cite
|
Sign up to set email alerts
|

Human antibodies reactive with purified envelope antigens of primate type C tumor viruses.

Abstract: Human sera from healthy individuals have been shown to react with viral antigens in preparations of de-tergent-disrupted C type viruses from monkeys. In this report, it is demonstrated that (populations of) these human antibodies react with highly purified envelope glycoproteins of the simian sarcoma virus-simian sarcoma-associated virus complex and the Friend leukemia virus complex. Several immunological parameters influencing human antibody binding to C type tumor virus antigens have been characterized. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
14
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…ized with R-MuLV (Hersh et al, 1974;Charman et al, 1975) were tested in the < assay, with similar results (Fig. 6) (Kurth et al, 1977;Kurth & Mikschy, 1978). Our interpretation of this binding is, however, very difficult, and conforms with that offered in more recent work (Barbacid et al, 1980;Snyder & Fleissner, 1980 (Yamaga et al, 1977).…”
Section: Methodssupporting
confidence: 68%
See 2 more Smart Citations
“…ized with R-MuLV (Hersh et al, 1974;Charman et al, 1975) were tested in the < assay, with similar results (Fig. 6) (Kurth et al, 1977;Kurth & Mikschy, 1978). Our interpretation of this binding is, however, very difficult, and conforms with that offered in more recent work (Barbacid et al, 1980;Snyder & Fleissner, 1980 (Yamaga et al, 1977).…”
Section: Methodssupporting
confidence: 68%
“…As most of these viruses are immunologically and biochemically similar, it was hoped that a putative human virus would follow the same pattern. The discrepancies between the reports have been ascribed to the use of different techniques, viral antigens and serum samples (Kurth et al, 1977;Kurth & Mikschy, 1978). Moreover, the specificity of these antibodies has been questioned (Hogg et al, 1979;Snyder et al, 1976).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, Kurth and Mikschy (20) reported that a large fraction of human sera were capable of precipitating, at relatively high titers, the purified major envelope glycoprotein (gp7O) of the woolly monkey type C virus. These workers ascribed discrepancies with previous reports (15) to the influence of variables on the antigen-antibody reactions (21).…”
mentioning
confidence: 99%
“…Purified RSV antigens and pp60 ~-src were iodinated by the chloramine T method and employed in RIPAs to test directly the specificity of monoclonal antibodies (Kurth & Mikschy, 1978). It proved to be advantageous to use either fresh, unfrozen monoclonal antibodies from ascites (as also observed by Lipsich et al, 1983) or aliquots frozen once only.…”
Section: Methodsmentioning
confidence: 99%